Analisis Ketersediaan Dan Kebutuhan Air Baku Kab. Bantaeng : Studi Kasus: Bendungan Karatuang, Kab. Bantaeng, Sulawesi Selatan - Sri Yusriyani; Andi Rumpang Yusuf; Suryani Syahrir (Jurnal Penelitian Teknik Sipil Konsolidasi, 2026)
Dams are built to hold and accommodate water and function as water catchers and to store them in the rainy season when river water flows in large quantities and exceeds requirements for irrigation, drinking water or industrial purposes. The Karatuang Dam, which is located in Bantaeng Regency, was built in the Calendu river basin, which has problems related to meeting the needs and availability of raw water. Bantaeng Regency often experiences drought during the dry season, which results in the land becoming very dry. So it is necessary to know how much the total raw water demand, water availability and reservoir capacity will be until 2042. It is necessary to research the population using arithmetic and geometric methods to find out how much increase will occur over the next 20 years. So it can be ascertained how large the population will be served until 2042 in Bantaeng Regency. It is necessary to research the annual maximum rainfall using several rainfall stations in this research to help determine adequate water needs. As well as, analyzing the frequency of rainfall using various methods including the gumbel distribution method, normal distribution method, log normal distribution method, Log Pearson Type III distribution method.